الزاد ال ر وحي وأثره على المردود الدعوي من خلال سورة المزمل - حليلو, شيماء; سليماني, فاطمة الزهراء; حمداوي, نزيهة (جامعة الوادي university of eloued, 2016)
لابد لأم ركح يراد بؽا أف تؤثر في كاقع ابغياة البشرية فتحوبؽا كجهة آخ رة, فلب بد بؽذه الركح من خلوة كعزلة ببعض الوقت كانقطاع عن شواغل الأرض كضجة ابغياة كبنو الناس الصغتَة التي تشغل ابغياة, كذلك بالصلبة كتلبكة القرآف كذكر الله إف ىذه ابػلوة ىي الزاد الركحي, كآثا ره ابؼتمثلة في برمل أمانة التوحيد الإبؽي, كالعبء الباىظ كابعهد ابؼرير, في برمل أعباء الرسالة, كدعوة عمو ابؼكلفتُ إلى سبل الوحدة الذاتية كإرشادىم بكوىا بالتصبر على أذيتهم كبرمل ابؼتاعب كابؼشاؽ في تبليغ الدّعوةAny soul that is intended to affect the reality of human life and turn it to another destination, this soul must be isolated and isolated by some time and the abandonment of the concerns of the earth and the fuss of life and the concerns of people who occupy life ... By prayer and recitation of the Koran and reminded God that this retreat is And the effects of carrying the secretariat of divine unification, and the heavy burden and bitter effort, to bear the burdens of the message, and call the general taxpayers to the ways of self-unity and guidance towards them to handle their abuse and bear the trouble and hardship in reporting the invitation.
دعوة